(untitled) (Oratio Directa, 2022)
This study examines the management strategies used by Media Indonesia Daily to sustain its print newspaper in the digital era. A descriptive qualitative approach was applied through semi-structured interviews with four organizational actors: a humaniora editor, an assistant head of circulation and distribution, an assistant research-and-development editor, and a journalist. The findings identify five mutually supporting practices: print-digital convergence through online news and e-paper services; journalist training and professional development; paid and non-paid distribution channels; data-based reporting supported by the research-and-development unit; and verification procedures involving relevant sources, recordings, and editorial review. The organization frames digital media as both a challenge and an opportunity rather than as a reason to discontinue print. Print and digital products are positioned as complementary channels for serving different reader needs. However, the source does not report interview dates, a coding procedure, circulation figures, revenue trends, audience measurements, or independent documentary evidence. Consequently, the results describe participants' organizational accounts and cannot establish the commercial effectiveness or long-term sustainability of the strategies.